2022
DOI: 10.2147/ndt.s377877
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Central Vein Sign as a Diagnostic Biomarker in Egyptian Patients with Multiple Sclerosis

Abstract: Purpose Magnetic resonance imaging (MRI) findings in multiple sclerosis (MS) overlap with numerous MS mimics. The central vein sign (CVS) can help to differentiate MS from other mimics. This study aimed to determine the value of CVS as a diagnostic biomarker for distinguishing MS from its mimics. Patients and Methods Patients were prospectively recruited into two groups: a typical clinical (TC) MS presentation with an atypical MRI for MS and an atypical clinical (ATC) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Our study showed that signi cantly lower of circMAN1A2 in gout patients than that in normal individuals, moreover, a high AUC of 0.86 (95% CI 0.66 to 1.00), and high sensitivity of 90.0%, speci city of 90.1% were found for circMAN1A2 in differentiating gout from the healthy controls. Sensitivity is the most important characteristic of a screening test, as its primary role is to identify samples for further diagnostic testing [37]. Thus, circMAN1A2 could be a potential diagnostic marker for gout detection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that signi cantly lower of circMAN1A2 in gout patients than that in normal individuals, moreover, a high AUC of 0.86 (95% CI 0.66 to 1.00), and high sensitivity of 90.0%, speci city of 90.1% were found for circMAN1A2 in differentiating gout from the healthy controls. Sensitivity is the most important characteristic of a screening test, as its primary role is to identify samples for further diagnostic testing [37]. Thus, circMAN1A2 could be a potential diagnostic marker for gout detection.…”
Section: Discussionmentioning
confidence: 99%